2019
DOI: 10.36834/cmej.52997
|View full text |Cite
|
Sign up to set email alerts
|

Medical students’ challenges and suggestions regarding research training: a synthesis of comments from a cross-sectional survey

Abstract: Background: We previously reported on a cross-sectional study of students from the Michael G. DeGroote School of Medicine at McMaster University that found most respondents wanted more opportunities to participate in research. Students provided additional comments that we synthesized to enrich the findings of our quantitative analysis.   Methods: From our previously administered 13-item, online questionnaire, run across three campuses in Ontario, Canada, 498 of 618 medical students completed our survey a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 13 publications
0
6
0
2
Order By: Relevance
“…La investigación permite al estudiante desarrollar el pensamiento crıtico y habilidades de evaluación, decidir una futura carrera relacionada a las ciencias básicas o la investigación clıńica, (10) Uno de los problemas es el tiempo de dedicación a la investigación ya que el plan de estudio no es �lexible, (13) lo que hace que el estudiante utilice el poco tiempo que le queda para realizar su tesis.…”
Section: Discussionunclassified
“…La investigación permite al estudiante desarrollar el pensamiento crıtico y habilidades de evaluación, decidir una futura carrera relacionada a las ciencias básicas o la investigación clıńica, (10) Uno de los problemas es el tiempo de dedicación a la investigación ya que el plan de estudio no es �lexible, (13) lo que hace que el estudiante utilice el poco tiempo que le queda para realizar su tesis.…”
Section: Discussionunclassified
“…Students performed relatively better in academic reading and writing, probably because the ve medical schools in this study all provided related compulsory courses. A Canadian study showed medical students' desire for a formalized research curriculum, centralized opportunities, and more help from experienced researchers [26]. Given the major obstacles and the special abilities these students are eager to improve, adjustments for the curriculum are essential and urgent.…”
Section: Discussionmentioning
confidence: 99%
“…Students performed relatively better in academic reading and writing, probably because the ve medical schools in this study all provided related compulsory courses. A Canadian study showed medical students' desire for a formalized research curriculum, centralized opportunities, and more help from experienced researchers [28]. Given the major obstacles and the special abilities these students are eager to improve, adjustments for the curriculum are essential and urgent.…”
Section: Discussionmentioning
confidence: 99%